Психология фанининг долзарб вазифаларидан бири - Турсунов, Л.С (SCIENCE and SOCIETY, 2024)
In the article, the main attention is focused on one of the current tasks of the science of psychology, and special aspects
Keywords: information storms; youth education; self-awareness; knowledge; mastery; decisions; dysfunctional families; interpersonal; attitude; national value; selflessness